Designing, constructing and evaluating a dynamic prototype dryer for obtaining rolled dehydrated fruit pulp (2011)
This paper describes how a functional prototype for a dynamic dryer was designed, along with its basic parts: drying tunnel, mechanical transport system for material inside the equipment and selecting and designing a system for supplying hot air. A simple transport mechanism was implemented which allowed combining two flow dispositions: parallel and countercurrent flow. Mango (Mangifera indica L) pulp was dehydrated using three dryer air temperatures (50°C, 60°C and 70°C) and three drying air speeds inside the dryer (1.6, 2.2, 3.4 m s-1) for evaluating the prototype. Propane gas was used as fuel for heating the air. The prototype design led to dehydrating fruit pulp having 4.26 bs smooth initial humidity content up to a 0.11 db final humidity content, with 8-hour drying time (70°C and 3.4 m s-1 air speed), assuming 4.5 0.5 mm pulp thickness, in 300 x 180 mm and 15 mm height rectangular trays. 1.5 0.5 mm thickness rolled dehydrated pulps were obtained in these conditions  The final product had 0.60a (aw) water activity providing for a stable product, having low water content and very similar characteristics to those of the fresh product (shown by Weende analysis).